A study of maintenance contribution to joint production and preventive maintenance scheduling problems in the robustness framework. (4th December 2009) - Benbouzid-Sitayeb, Fatima; Bendjoudi, Ahcene; Benkhellat, Samir; Varnier, Christophe; , Noureddine Zerhouni
In this paper, we deal with a joint production and Preventive Maintenance (PM) scheduling problem in the robustness framework. The contributions of this paper are twofold. First, we will establish that the insertion of maintenance activities during production scheduling can hedge against some changes in the shop environment. Furthermore, we will check if respecting the optimal intervals of maintenance activities guarantees a minimal robustness threshold. Then, we will try to identify from the used optimisation criteria those that allow making predictive schedules more robust. The computational experiments in a flowshop show that joint production and PM schedules are more robust than production schedules and maintenance provides an acceptable tradeoff between equipment reliability and performance loss under disruption.